Generation of human iPSC-derived pancreatic organoids to study pancreas development and disease [version 1; peer review: 2 approved, 2 approved with reservations] - Francesca Maria Spagnoli; Abigail Isaacson; Jean-Francois Darrigrand (F1000Research)
The pancreas has vital endocrine and exocrine functions that can be affected by life-threatening diseases such as diabetes and pancreatic cancer. Although animal models are essential for understanding pancreatic development and disease, they are limited by their low throughput and major species-specific molecular and physiological differences. Generating 3D in vitro models, such as organoids, that are physiologically relevant is essential for investigating pancreatic development and disease in the human context. However, the production of human stem cell-derived pancreatic organoids with a proper branched architecture and correct patterning of cell domains remains challenging. Here, we successfully developed a protocol that efficiently and reproducibly generated organoids from human induced pluripotent stem cells (hiPSCs) by optimizing organoid culture format and media. Our differentiation protocol promotes acinar cell differentiation and generates organoids with branches patterned into the central trunk and peripheral tip domains without relying on animal-derived matrices for organoid culture. This platform opens the door to high-throughput investigations of human pancreatic development in a system that recapitulates the most important aspects of pancreatic tissue architecture. Lastly, we anticipate that this system will contribute to the replacement of animal models used to investigate diseases, such as pancreatic cancer.